Advertising practices and promotion in the Islamic World under the Shariah observation: a case study on Bank Islam in Malaysia - Haque, A. K. M. Ahasanul; Mohd. Israil, Khaliq Ahmad; Jahan, Syeada Irfath (Indian Journal of Marketing, 2009)
Functions of Islamic banking needs more refinement and preciseness for serving greater Ummatic interest. This study related to the advertising and promotion of Islamic banking services in Malaysia...